Mapping Safety through an Intersectional Perspective. The Case of Wher - Dambrosio Clementelli, Alina (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
This contribution aims at critiquing the hegemonic discourse and urban policies on women’s safety in the Italian context. Adopting the intersectional approach (Collins & Guo 2021, Anthias 2013) allows for highlighting how processes of racialisation and gender structure the conceptualisation of security in urban space. In recent years, several policies have focused on urban security as a criterion to be pursued in city governance and at the same time the adoption of gender mainstreaming policies to improve the relationship between women and the city. However, security policies have been translated into an emergency and securitarian approach, homogenising different phenomena such as immigration and male violence against women. The discourse that emerges is not only marked by the link between racism and sexism but also makes male violence against women a public order issue and women a homogeneous group without considering the intertwining of gender with other categories. Through the case study of a women’s safety app, "Wher, the representation of safety and how this conditions everyday practices will be analysed. The app is based on user comments and aims to suggest the safest ways for women and the creation of a user community. Referring to the literature on safety and gender (Valentine 1989, Koskela) 2002), the attempt will be to show which dynamics emerge and to whom these measures are addressed. Finally, as the literature has increasingly recognised the interactive nature of public and private spaces, I propose to adopt social reproduction as an approach to enable critical discourse on women’s ideas of safety, how safety and danger are produced in different ways, in different places and at different scales, as experienced and understood by women themselves in their everyday lives.